2015
DOI: 10.5539/jsd.v8n1p108
|View full text |Cite
|
Sign up to set email alerts
|

Local Spatially Dependent Driving Forces of Urban Expansion in an Emerging Asian Megacity: The Case of Greater Jakarta (Jabodetabek)

Abstract: Urban expansion and urbanization have been continuing to grow rapidly, especially in Asian megacities. Greater Jakarta (Jabodetabek) has emerged as the world's second largest urban area, with a population of 28 million in 2010, where urban expansion has a significant impact on the local as well as the global environment. Efforts to control urban expansion must start from a clear understanding of its various driving forces at a local, regional, and global level. Studies of the interdependencies between these dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 30 publications
0
24
2
7
Order By: Relevance
“…For example, Jakarta, obtaining the world's second largest urban area with a population of 28 million, has yet to have any quantitative urban area delineation [69,70]. Identification of actual urban growth in developing cities is vital to city planners, environment managers and policy makers due to the difference between planned growth and actual growth [14].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jakarta, obtaining the world's second largest urban area with a population of 28 million, has yet to have any quantitative urban area delineation [69,70]. Identification of actual urban growth in developing cities is vital to city planners, environment managers and policy makers due to the difference between planned growth and actual growth [14].…”
Section: Discussionmentioning
confidence: 99%
“…The JMA includes Jakarta, the capital city of Indonesia, and its suburban area and consists of the capital special province (DKI Jakarta), five municipalities (Tangerang, Tangerang Selatan, Depok, Bekasi, and Bogor) and three districts (Tangerang, Bekasi, and Bogor) (Figure 1). Its population agglomeration is one of the highest in the world [49] and it has experienced rapid urban expansion [46]. This region had a population of 27.2 million people in 2011 [47] and covers a total area of 6659 km 2 .…”
Section: Study Areamentioning
confidence: 99%
“…In the JMA, ISA has rapidly increased over several decades [46][47][48]. The JMA includes Jakarta, the capital city of Indonesia, and its suburban area and consists of the capital special province (DKI Jakarta), five municipalities (Tangerang, Tangerang Selatan, Depok, Bekasi, and Bogor) and three districts (Tangerang, Bekasi, and Bogor) (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…Data on the period from 1972 until 2010, for example, indicated that the urban area of Jakarta and its surroundings, namely the JakartaBogor-Depok-Tangerang-Bekasi (Jabodetabek) region had increased by more than 2,096 km 2 , as a result of urbanization process Pravitasari et al, 2015). The pace of development of Jakarta has induced rapid land use changes in the surrounding area.…”
Section: Introductionmentioning
confidence: 99%
“…The state capital of Indonesia, Jakarta, has been developing very rapidly to become the second largest metropolitan area in the world after Tokyo (Fukami et al, 2014;Pravitasari et al, 2015). Data on the period from 1972 until 2010, for example, indicated that the urban area of Jakarta and its surroundings, namely the JakartaBogor-Depok-Tangerang-Bekasi (Jabodetabek) region had increased by more than 2,096 km 2 , as a result of urbanization process Pravitasari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%